Qualidade de rapaduras enriquecidas com farelo de arroz extrusado e amêndoas de baru/amendoim torrados - SILVA, Célia Caroline Florindo da (2012)
The purpose of this research was to develop, using a mixture design, rapadura enriched with rice bran extruded and baru almonds/peanuts roasted in different proportions, and characterize them in relation to their properties, chemical, physical (texture and parameters of color), microbiological and sensory, comparing them to standard rapadura, composed only of sugar cane juice. With the insertion of the mixture of rice bran extruded and baru almonds/peanuts roasted in formulated rapadura, it was observed that the greater the amount of rice bran extruded under sugar cane juice concentrated tended to the higher ash concentration. The highest levels of proteins, lipids and total dietary fiber were observed when the formulations had higher amounts of baru almonds/ peanuts roasted and rice bran extruded under sugar cane juice concentrated. Regarding the brightness, the rapadura made with baru almond toast and extruded rice bran showed the highest upward trend in higher levels of extruded rice bran and baru almond toast, those made with roasted peanuts and rice bran extruded. This trend was observed in the largest quantities of rice bran and extruded under roasted peanuts and sugar cane juice sugar-concentrated. As for the texture maximum compression force had a greater tendency to increase when the values of sugar cane juice concentrated and baru almond roasted were intermediate and the formulation of peanuts, the smaller the amount of roasted peanuts and sugar cane juice sugar-concentrated and larger extruded rice bran. As the pattern is regarded as a molasses feed unbalanced due to the caloric value to be assigned, almost exclusively to the carbohydrate to the low protein content and the absence of lipids, it can be concluded that with the addition of the mixture of rice bran and extruded baru almonds roasted, the brown sugar has become a more complete food, watching other nutrients, lipids and proteins from rice bran extruded and baru almonds roasted, as well as fibers, which contribute to the better functioning of the organism human.